Numerical Reconstruction of the Masina Lekh Hailstorm Event - Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
The atmospheric conditions leading to the hailstorm over the Mt. Masina Lekh ( 1800 m) and its immediate surroundings has been numerically simulated by implementing the Advance Weather Research and Forecasting (WRF) modeling system. The distribution of cloud water-mixing ratio and numerical sounding profiles strongly suggest massive scale hailstorm in and around the Mt. Masina Lekh. The atmosphere over the area was fully saturated with cloud-water mixing ratio exceeding 1.42 g kg-1and the temperature at the top of the Mt. Masina Lekh ( 800 hPa) remained close to the freezing and decreased quickly to freezing aloft and reached to -22°C at the top of the cloud around 550 hPa. The massive scale vertical convection induced by the Mt. Masina Lekh appears to be one of the main reasons for the occurrences of frequent and localized severe hailstorms over the area. Journal of Institute of Science and Technology, 2015, 20(2): 49-53